Achieving very bright mechanoluminescence from purely organic luminophores with aggregation-induced emission by crystal design. Issue 8 (11th May 2016) - Xu, Bingjia; Li, Wenlang; He, Jiajun; Wu, Sikai; Zhu, Qiangzhong; Yang, Zhiyong; Wu, Yuan-Chun; Zhang, Yi; Jin, Chongjun; Lu, Po-Yen; Chi, Zhenguo; Liu, Siwei; et al.
Abstract : An effective strategy for the molecular design of AIE-ML materials is demonstrated based on tetraphenylethene with formyl substituents. Abstract : Although bright organic mechanoluminescence (ML) has been observed for a few luminophores with aggregation-induced emission (AIE), details of the positive effect of AIE on ML performance remain unclear and a feasible design principle for AIE-ML compounds has not yet been presented. Herein, an effective strategy for the molecular design of efficient AIE-ML materials is demonstrated, based on tetraphenylethene (TPE) building blocks with formyl substituents, which yield non-centrosymmetric crystal structures with prominent piezoelectric properties for molecular excitation combined with AIE features for intense emission. Following this approach, three AIE-active compounds have been developed and are found to show unique ML characteristics. Furthermore, the results of single crystal X-ray analysis and density functional theory (DFT) calculations suggest that the ML performance would probably be further enhanced by creating molecules with larger dipolar moments and enhanced AIE properties.